2004
DOI: 10.1002/sia.1692
|View full text |Cite
|
Sign up to set email alerts
|

Time‐of‐flight atom‐probe field ion microscope studies of surface‐related phenomena

Abstract: The time-of-flight atom-probe field ion microscope is both a single-atom detection sensitivity mass-tocharge ratio analyser and an ion energy analyser, provided that the instrument resolution is good enough. Its major applications are in material analysis. However, it has been used also for studying surface-related phenomena such as surface segregation of alloys, mechanisms of ion formation in field desorption, novel ion and cluster ion formation in laser-stimulated field ion emission, field dissociation of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
2
0
1
Order By: Relevance
“…is even evidence for a field dependent (FD) neutralization. The analysis of the ESFD of 22 Ne and 20 Ne revealed that below 4.5 V/Å the heavier 22 Ne is less abundant than expected from the natural isotopic abundance of 8.8%. 18 Owing to its higher mass, this isotope stays longer in the re-neutralization zone and therefore has a higher probability of being quenched.…”
Section: Photon-induced No Field Desorptionmentioning
confidence: 82%
See 1 more Smart Citation
“…is even evidence for a field dependent (FD) neutralization. The analysis of the ESFD of 22 Ne and 20 Ne revealed that below 4.5 V/Å the heavier 22 Ne is less abundant than expected from the natural isotopic abundance of 8.8%. 18 Owing to its higher mass, this isotope stays longer in the re-neutralization zone and therefore has a higher probability of being quenched.…”
Section: Photon-induced No Field Desorptionmentioning
confidence: 82%
“…To elucidate the reason for this weak binding of NO at the Rh surface, an analysis by laser-induced field evaporation was performed. 21,22 At 2.5 V/Å and 20 J/cm 2 , a spectrum of surface species was obtained as shown in Fig. 10.…”
Section: Photon-induced No Field Desorptionmentioning
confidence: 99%
“…Foi observado por Tsong e colaboradores o aparecimento de um comportamento oscilatório na composição de ligas próximo à superfície como, por exemplo, em ligas metálicas do tipo Pt-Rh e Pt-Ni, em que as composições do Rh e do Ni variam plano a plano, a partir da superfície, de forma decrescente em relação à concentração do volume [20,21].…”
Section: Introductionunclassified